Pharmacognostic studies on three species of Spermacoce - Shan Fan; Wenfeng Weng; Shengguo Ji (KeAi Communications Co., Ltd., 2024)
To provide a scientific basis for identification of Spermacoce species, including Spermacoce remota Lamarck, Spermacoce exilis (L. O. Williams) C. D. Adams, and Spermacoce alata Aubl., the current study was carried out for pharmacognostical parameters. Roots, stems, and leaves of plants were collected for pharmacognostical studies involving source identification, microscopic evaluation, character observation, phytochemical screening, ultraviolet spectrum and molecular pharmacognosy analysis. S. remota, S. alata, and S. exilis belong to the same genus, and the morphology of the plants was similar. Powder microscopy showed the presence of fibers, needle crystal bundles, spiral vessels, and near spherical pollen grains in all the plants. Phytochemical investigation demonstrated that S. remota, S. alata, and S. exilis all contained glycosides, proteins and volatile oils. In addition, the extracts of S. alata and S. exilis revealed the presence of flavonoids and tannins. In this study, the ITS sequence of S. exilis was found for the first time which had been submitted to NCBI to obtain the GenBank registration number. The results of neighbor-joining phylogenetic tree showed that S. exilis, S. remota and S. alata could be distinguished accurately. The study will be beneficial to the identification, resource conservation and quality control of Spermacoce species.